2016
DOI: 10.1126/sciadv.1600031
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear respiratory factor 1 and endurance exercise promote human telomere transcription

Abstract: The AMPK/PGC-1α metabolic pathway and nuclear respiratory factor 1 up-regulate human telomere transcription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 45 publications
1
90
0
1
Order By: Relevance
“…To investigate single-telomere TERRA molecules in human cancer cells, we employed the CRISPR/Cas9 genome editing tool to promote site-specific integration of a cassette containing 10×MS2 repeats and a neomycin resistance gene flanked by lox-p sites (TERRA-MS2 cassette) at subtelomere 15q in AGS cells, which is a human stomach adenocarcinoma cell line. The subtelomere 15q was chosen since expression of TERRA from human telomere 15q has been extensively validated by in vitro techniques [12,16,18,28]. The 15q subtelomere contains a conserved CpG rich TERRA promoter region and the TERRA transcription start sites within this subtelomere have been mapped [7,18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate single-telomere TERRA molecules in human cancer cells, we employed the CRISPR/Cas9 genome editing tool to promote site-specific integration of a cassette containing 10×MS2 repeats and a neomycin resistance gene flanked by lox-p sites (TERRA-MS2 cassette) at subtelomere 15q in AGS cells, which is a human stomach adenocarcinoma cell line. The subtelomere 15q was chosen since expression of TERRA from human telomere 15q has been extensively validated by in vitro techniques [12,16,18,28]. The 15q subtelomere contains a conserved CpG rich TERRA promoter region and the TERRA transcription start sites within this subtelomere have been mapped [7,18].…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, TERRA molecules consist of subtelomere derived sequences at their 5′ end, and their 3′end includes arrays of UUAGGG repeats (reviewed in [8]). Expression of TERRA is tightly regulated by the activity of several transcription regulators, including the chromatin organizing factor CTCF [9] and the transcription factors heat shock factor 1 (HSF1) [10], Snail [11], as well as the nuclear respiratory factor NRF1 [12]. Furthermore, telomere shortening is associated with increased TERRA levels in yeast as well as human cells [13-16].…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the majority of TRLs form cotranscriptionally, can we expect the subtelomeric component of TERRA to influence TRL formation? Most TERRA promoters are embedded in regions positioned within 2 kb of the telomere tract , although TERRA promoters positioned 5–10 kb from the telomere tract have been described for several human telomeres . Despite sharing high sequence similarity , a bioinformatic analysis of the distal 2 kb of the majority of human chromosome ends revealed that subtelomeres differ in characteristics such as CpG richness, GC content, and GC‐skewing .…”
Section: Telomere R‐loops In Mammalsmentioning
confidence: 99%
“…Assuming that the majority of TRLs form cotranscriptionally, can we expect the subtelomeric component of TERRA to influence TRL formation? Most TERRA promoters are embedded in regions positioned within 2 kb of the telomere tract [86,102,103], although TERRA promoters positioned 5-10 kb from the telomere tract have Fig. 1.…”
Section: How Do Subtelomeric Regions Contribute To Trl Formation?mentioning
confidence: 99%
“…The report of Jarosch et al (2016) and many others highlight the fact that mitochondrial signaling plays a functional role in promoting exercise efficiency. Both NRF-1 and PGC1α stimulate human telomere transcription in response to exercise via AMPK activation, connecting telomere protection in aging with metabolism (Diman et al, 2016). Increase in the ADP/ATP ratio that follows physical activity induces AMPK activity in muscle, and, in so doing, regulates the β-oxidation capacity of muscle and mitochondrial biogenesis (Winder et al, 1997; Zong et al, 2002).…”
Section: Muscle Metabolism In Agingmentioning
confidence: 99%